1998
DOI: 10.1590/s0001-37141998000300002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Activity of Dark Red Latosol Samples Stored at Different Temperatures

Abstract: The enzymatic activity of soil samples stored at temperatures of 5 to -12oC and at room temperature for 0-32 weeks was determined. While alkaline phosphatase and dehydrogenase activity was decreased compared to control in samples stored at low temperatures, acid phosphatase activity showed no significant change.
Foi determinada a atividade enzimática de amostras de solo armazenadas às temperaturas de 5, -12oC e ambiente durante 0-32 semanas. A atividade da fosfatase alcalina e da desidrogenase diminuiu nas …
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been suggested by some researchers that enzyme activity is not affected by quick freezing (Asmar et al, 1995;Kandeler et al, 2002). On the other hand, Vieira and Nahas (1998) have shown that alakaline phosphatase and dehydrogenase activity were substantially reduced even during storage at )12°C. Nevertheless, it is widely accepted that freezing is a non-destructive procedure for molecular analyses, which allows looking more closely at gradients of microbial species or communities that are enriched or depleted across the rhizosphere.…”
Section: Resultsmentioning
confidence: 98%
“…It has been suggested by some researchers that enzyme activity is not affected by quick freezing (Asmar et al, 1995;Kandeler et al, 2002). On the other hand, Vieira and Nahas (1998) have shown that alakaline phosphatase and dehydrogenase activity were substantially reduced even during storage at )12°C. Nevertheless, it is widely accepted that freezing is a non-destructive procedure for molecular analyses, which allows looking more closely at gradients of microbial species or communities that are enriched or depleted across the rhizosphere.…”
Section: Resultsmentioning
confidence: 98%